The relationship of Adiponctin / Leptin ratio with metabolic syndrome - Turki, Kismat M.; Mohammed, Suma H.; Abdul-Qahar, Zina H. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Metabolic syndrome is a cluster of risk factors for atherosclerotic cardiovascular disease caused by abdominal obesity, such as hyperglycemia, hypertension, dyslipidemia, and insulin resistance.Adiponectin is a protein hormone that modulates a number of metabolic processes, including glucose regulation and fatty acidcatabolism. Adiponectin is exclusively secreted from adipose tissue into the bloodstream. Leptin, a hormone synthesized by fat tissue had been noted to regulate energy balance and metabolism.In this study investigated the relationships of adiponectin/leptin ratio with metabolic syndrome in apparently healthy Iraqi male adults. Objective: This study was designed to investigate the relationship of adiponectin/leptin ratio with metabolic syndrome in apparently healthy Iraqi male adults. Methods: Ninety male subjects were enrolled in study (mean age, 40.97 ± 7.94 years). Serum leptin level and adiponectin level were measured using an enzyme-linked immunosorbent assay. And the presence of metabolic syndrome was assessed. Results: Mean leptinlevel was significantly higher (7.29 ± 0.38 ng/ml), whileadiponectin andadiponectin/leptinratio was significantly lower(4.78 ± 0.24 μg/ml; 0.74 ± 0.07) respectively in subjects with MS. With increasingnumber of metabolic syndrome components, the mean values of leptinincreased and the adiponectin andadiponectin/leptindecreased. Conclusion: adiponectin/leptinratio correlated well with the presence and number of metabolic syndrome components in Iraqi male subjects.